Pegcetacoplan versus eculizumab in patients with paroxysmal nocturnal haemoglobinuria (PEGASUS): 48-week follow-up of a randomised, open-label, phase 3, active-comparator, controlled trial. Issue 9 (September 2022) - de Latour, Régis Peffault; Szer, Jeff; Weitz, Ilene C; Röth, Alexander; Höchsmann, Britta; Panse, Jens; Usuki, Kensuke; Griffin, Morag; Kiladjian, Jean-Jacques; de Castro, Carlos M; Nishimori, Hisakazu; Ajayi, Temitayo; et al.
Summary: Background: In the PEGASUS trial, the complement C3 inhibitor, pegcetacoplan, showed superiority to eculizumab in improving haematological outcomes in adult patients with paroxysmal nocturnal haemoglobinuria and suboptimal response to eculizumab at 16 weeks. The aim of the open-label period was to evaluate the long-term efficacy and safety of pegcetacoplan through to 48 weeks. Methods: PEGASUS was a phase 3, randomised, open-label, active-comparator controlled trial conducted in 44 centres in Australia, Belgium, Canada, France, Germany, Japan, Russia, South Korea, Spain, the UK, and the USA. Eligible participants were aged 18 years or older, had paroxysmal nocturnal haemoglobinuria, and had a haemoglobin concentration of less than 10·50 g/dL after 3 months or longer of stable eculizumab treatment. After a 4-week run-in with eculizumab plus pegcetacoplan, patients were randomly assigned (1:1) by interactive response technology to pegcetacoplan (1080 mg subcutaneously twice weekly) or eculizumab (according to their regimen at enrolment) for 16 weeks and could continue to the open-label period (32 weeks of pegcetacoplan monotherapy [pegcetacoplan-to-pegcetacoplan] or 28 weeks of pegcetacoplan monotherapy [eculizumab-to-pegcetacoplan]). Randomisation was stratified by platelet count and number of previous blood transfusions. The primary endpoint was change from baseline in haemoglobin at week 16, which has previously been reported. The outcomes of the open-label period (week 16 to week 48) are reported here. At 48 weeks, efficacy (including mean haemoglobin concentration and quality of life measured on the Functional Assessment of Chronic Illness Therapy [FACIT]-Fatigue scale) was assessed in the intention-to-treat population and safety was assessed per protocol. This trial was registered with ClinicalTrials.gov, NCT03500549, and has been completed. Findings: Between June 14, 2018, and Nov 14, 2019, 80 patients were randomly assigned to receive treatment with pegcetacoplan (41 patients) or eculizumab (39 patients). Most participants were women (49 [61%]) and 31 (39%) were men; 12 (15%) were Asian, two (3%) were Black, 49 (61%) were White, and 17 (21%) were another race or did not report their race. The open-label period had 77 participants (38 pegcetacoplan-to-pegcetacoplan, 39 eculizumab-to-pegcetacoplan). Patients in the pegcetacoplan-to-pegcetacoplan group maintained high mean haemoglobin concentrations between 16 weeks (11·54 g/dL [SD 1·96]) and 48 weeks (11·30 g/dL [1·77]; p=0·14). Patients in the eculizumab-to-pegcetacoplan group had significantly greater mean haemoglobin concentrations at 48 weeks (11·57 g/dL [2·21]) versus 16 weeks (8·58 g/dL [0·96]; p<0·0001). Clinically meaningful improvements in FACIT-Fatigue scores were observed at 48 weeks, with a mean change from baseline for all patients receiving pegcetacoplan monotherapy of 9·89 points (SD 9·63), for patients in the pegcetacoplan-to-pegcetacoplan group mean 10·14 points (9·06), and for patients in the eculizumab-to-pegcetacoplan group mean 9·62 points (10·34). During the entire study period, 13 (16%) of 80 patients discontinued treatment (three [7%] of 41 through to week 16 due to breakthrough haemolysis, and ten [13%] of 77 due to severe treatment-emergent adverse events) and 18 patients (eight pegcetacoplan-to-pegcetacoplan, ten eculizumab-to-pegcetacoplan) had at least one serious treatment-emergent adverse event during the open-label period, four were considered to be related to pegcetacoplan treatment. The most common treatment-emergent adverse events (in ≥10% patients) among both pegcetacoplan-treated groups during the open-label period were injection site reactions (in 20 [26%] of 77 patients), haemolysis (15 [19%]), nasopharyngitis (12 [16%]), and diarrhoea (ten [13%]). No treatment-related deaths occurred throughout the duration of the study. Interpretation: The durability of improved haematological outcomes and favourable safety profile over 48 weeks of treatment suggests that pegcetacoplan has the potential to improve treatment benefit and alter treatment goals in patients with paroxysmal nocturnal haemoglobinuria. Funding: Apellis Pharmaceuticals.